Ramsay Hunt Syndrome with Oral Findings: A Rare Case - Eninanç, İlknur; Şahin, Büşra (Journal of Dentistry Indonesia, 2023)
Ramsay Hunt syndrome (RHS) is a disease that is caused by the varicella-zoster virus and is characterized by severe ear pain, auricular vesicular eruptions, and peripheral facial paralysis. Objective: The aim of this case report is to provide information about the clinical findings and treatment process of RHS, which is a rare case and may have oral findings and stress the importance of early diagnosis. Case Report: A 60-year-old male patient had previously consulted an otolaryngologist and a family physician with complaints of vesicular eruptions in the right ear auricle and on the mandible. The patient in whom a diagnosis could not be established presented to the Department of Oral and Maxillofacial Radiology after exacerbated lesions. White plaque-like and ruptured vesicular lesions were observed in the intraoral examination. All vesicular lesions were on one side of the face, and the patient was referred to the dermatology clinic with the diagnosis of RHS. Facial paralysis fully recovered in a short time after early diagnosis and treatment. It should be kept in mind that there may also be oral findings in RHS, and a patient’s intraoral and extraoral examination findings should be evaluated together. Conclusion: Early diagnosis and treatment are highly important in preventing complications such as permanent facial paralysis, vestibulocochlear dysfunction, and hearing loss